2021
DOI: 10.1021/acsaem.1c01270
|View full text |Cite
|
Sign up to set email alerts
|

High Sodium-Ion Conductivity in Interlocked Quaternary Chalcogenides Built with Supertetrahedral Building Units

Abstract: Herein, we report the syntheses, structure, Na-ion conductivity, and theoretical investigation of two moisture stable quaternary compounds, Na3ZnGaQ 4 (Q = S, Se). These compounds are synthesized using high-temperature solid-state synthesis routes employing polychalcogenide flux or by metathesis reactions. The crystal structure of these compounds is built up of a three-dimensional (3-D) network of corner-shared supertetrahedral (T2) units, where two such 3-D networks are interlocked. The d-block metal and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…two orders of magnitude higher (0.12 mS cm −1 ) than that of the former (0.37 mS cm −1 ). 40 Such a large difference in Na + conduction cannot be explained solely by a soer anionic sublattice in Na 3 ZnGaSe 4 , because the substitution of S with Se generally leads to a marginal increase in the s ion of SSEs. 26,28,41 For example, Bernges et al found that the concept of "the soer the lattice, the better" does not always hold true in the Li superionic conducting argyrodite Li 6 PS 5−x Se x Br.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…two orders of magnitude higher (0.12 mS cm −1 ) than that of the former (0.37 mS cm −1 ). 40 Such a large difference in Na + conduction cannot be explained solely by a soer anionic sublattice in Na 3 ZnGaSe 4 , because the substitution of S with Se generally leads to a marginal increase in the s ion of SSEs. 26,28,41 For example, Bernges et al found that the concept of "the soer the lattice, the better" does not always hold true in the Li superionic conducting argyrodite Li 6 PS 5−x Se x Br.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds were initially synthesized to investigate magnetic frustration and for the discovery of new functional materials that benet from unusual structural features. 38,39 Soon aer the introduction of these SSEs, Na + -conducting behaviors in Na 3 ZnGaS 4 and Na 3 ZnGaSe 4 were examined for possible use as Na + -conducting SSEs, 40 and s ion values of 0.37 mS cm −1 and 0.12 mS cm −1 were reported at RT, respectively. The authors addressed that a difference of ca.…”
Section: Introductionmentioning
confidence: 99%
“…95 Moreover, they also found that Na 3 ZnGaS 4 could have a higher ionic conductivity when exposed to air with a value of 0.13 mS/cm. 95 Figure 9 shows the Arrhenius plot for several solid state sodium-ion conductors. 93…”
Section: Solid-state Sodium-ion Electrolytesmentioning
confidence: 97%
“…Balijapelly et al recently revealed novel sulfide-based sodium electrolytes, Na 3 ZnGaS 4 and Na 3 ZnGaSe 4 , which had ionic conductivities of 3.74 × 10 –4 and 0.12 mS/cm at 30 °C, respectively . Moreover, they also found that Na 3 ZnGaS 4 could have a higher ionic conductivity when exposed to air with a value of 0.13 mS/cm Figure shows the Arrhenius plot for several solid state sodium-ion conductors …”
Section: Solid-state Sodium-ion Electrolytesmentioning
confidence: 99%
“…Multinary metal chalcogenide compounds have received considerable attention owing to their easily tunable structure, composition and morphology, as well as the resulting unique physical and chemical properties, [1][2][3][4][5][6] enabling extensive applications in many fields, such as photovoltaics, [7][8][9] illumination, 10 photocatalysis, [11][12][13] electrocatalysis, [14][15][16] sodium-ion batteries, 17,18 sensors, 3 biology, 19 medical 20 and so on. With the transition from the simplest binary elemental compositions to more complex multiple compositions through doping or alloying, the properties and applications of materials have undergone an interesting evolution, [21][22][23][24] such as ternary I-III-VI 2 group CuInS 2 (CIS) semiconductors, 25 I-III-VI 2 group alloyed Cu(In,Ga)(Se,S) 2 (CIGS) semiconductors, 26,27 and quaternary I 2 -II-IV-VI 4 group Cu 2 ZnSnS 4 (CZTS) semiconductors 28 etc., due to their ability to allow wide band gap modulation, high absorption coefficients, and lower toxicity compared with Cd/Pb compounds.…”
Section: Introductionmentioning
confidence: 99%